Factors influencing the consumption of digital music for women in South Africa - Mokwele, Thabo Emmanuel (My University, 2018)
This is a research report for a study to investigate the factors that influence the consumption of digital music for women in South Africa, in order to better understand their implications for technology design and online shopping behaviour. Online shopping, with its convenience and conjectured enjoyment, shows a slow uptake in South Africa and hypothetically the rest of the developing world. Parallel to that is the growing influence of women in the market place. Women being the largest consumer group in most markets and the only middle class segment that is growing in the economy globally, both these contexts presented an interesting case for research. This study therefore used music, as a hedonic instrument, to investigate factors that influence online behavioural intention for women in South Africa. The study will use a largely welcomed model, the Unified Theory on Acceptance and Use of Technology (UTAUT) by Venkatesh et al (2012) to study two age cohorts, Generation X and Y. The study measures Effort Expectancy, Habit, Hedonic Use and Online Risk as antecedents to behavioural intention for a female consumer to use an online shopping system. The results will later show that some of the hypothesis from the model are nullified and others have a negative effect to consumer online behaviour. Key words: Digital Consumption, Music, Hedonic, Behavioural Intention, Perceived Risk, Habit, Women, Technology Use, Online Behaviour, Effort Expectancy.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing
Keywords: Music--Computer network resources; Music and technology; Music--Computer programs